Experimental study of coconut (Cocos nucifera) waste through densification to obtain pellets and briquettes - Luis Velázquez-Araque; Jonathan Teneta-Ibarra; Fernando Sáenz-Gómez (Revista Facultad de Ingeniería Universidad de Antioquia)
In Ecuador, extensive coconut (Cocos nucifera) harvesting generates large quantities of waste, including husks, shells, and fibers, posing environmental and economic challenges. This study explores the densification of coconut waste (CW) into pellets and briquettes to address these issues. The process involved raw material collection, pre-treatment, drying, grinding, sieving, mixing, pelletizing, and briquetting, using cassava starch (CS) as a binder. Two CW-to-CS compositions were tested for each type of fuel. Key physical and combustion properties, such as higher heating value, moisture, volatile matter, fixed carbon, ash content, bulk density, and friability, were analyzed. Results showed that the PCA91 pellet sample (90% CW, 10% CS) achieved the best performance with a higher heating value of 15,350 J/g and 11.54% moisture content. Similarly, the BCA91 briquette sample (90% CW, 10% CS) demonstrated better performance with a heating value of 14,950 J/g and 13.75% moisture content. Most samples met the heating value and bulk density requirements of the Swedish SS187120 and Colombian NTC 2060 standards, although some fell short on ash, volatile matter, and fixed carbon content. Adjusting the CW-to-CS ratio could optimize biofuel properties, balancing energy output and stability, highlighting coconut waste’s potential as a sustainable biofuel.